Answers

2015-09-25T15:12:04+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Proof :- 

In quad ABCD ( See the given Figure ) ,We can find two triangles - ΔBCD & ΔABD

→ Now , In ΔBCD

∠BDC > ∠ CBD{ Angles opposite to smaller side is smaller } → 1st Equation

Now , In Δ ABD 

∠ADB > ∠ABD { Angles opposite to smaller side is smaller } → 2nd Equation

Let us now add the first two equations respectively ,

→ ∠ BDC + ∠ADB   >   ∠CBD  + ∠ ABD

→ ∠ ABC  > ∠ ADB 

⇒ Hence proved that ∠ B  > ∠ D
0